2021
DOI: 10.1111/trf.16551
|View full text |Cite
|
Sign up to set email alerts
|

Process and procedural adjustments to improve CD34+ collection efficiency of hematopoietic progenitor cell collections in sickle cell disease

Abstract: Background: Adequate CD34+ collection efficiency (CE) is critical to achieve target CD34+ cell doses in hematopoietic progenitor cell (HPC) collections. Autologous HPC collection in sickle cell disease (SCD) is associated with unstable collection interfaces and low CD34+ CEs. We hypothesized that variables specific to SCD, activation of blood cells and elevated viscosity, might contribute to these issues and made adjustments to the collection process and procedure to address our hypothesis. Study design and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…Esrick et al adjusted the depth of the collection toward the RBC layer by using 5%–10% interface collection, and the CEs of two collections exceeded 40% 3 . Avecilla et al lowered CP to 15–25 and 17–25 for two patients, and reached a CE1 of 70% and 51% respectively 8 . In this study, we identified the optimal collection depth to capture SCD HSPCs and achieved highly efficient apheresis collection.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Esrick et al adjusted the depth of the collection toward the RBC layer by using 5%–10% interface collection, and the CEs of two collections exceeded 40% 3 . Avecilla et al lowered CP to 15–25 and 17–25 for two patients, and reached a CE1 of 70% and 51% respectively 8 . In this study, we identified the optimal collection depth to capture SCD HSPCs and achieved highly efficient apheresis collection.…”
Section: Discussionmentioning
confidence: 85%
“…HbS < 10%, does not necessarily improve CE either 3 . Avecilla et al reported that percentage of HbS of a HSPC product was 91, whereas percentage of HbS of the HSPC donor's peripheral blood was 22, indicating that sickle RBCs could have a similar sedimentation rate as HSPCs or form aggregates with HSPCs 8 . Hence, sickle RBCs, even when present at a low percentage, can profoundly affect HSPC collection, and adjusting the apheresis setting is needed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations